Wnt/β-Catenin Signaling Pathway in the Development and Progression of Colorectal Cancer - He K; Gan WJ (Cancer Management and Research, 2023)
Kuang He, Wen-Juan Gan Department of Pathology, Dushu Lake Hospital Affiliated of Soochow University, Suzhou, Jiangsu, People’s Republic of ChinaCorrespondence: Wen-Juan Gan, Department of Pathology, Dushu Lake Hospital Affiliated of Soochow University, Suzhou, Jiangsu, 215124, People’s Republic of China, Tel +86 0512-65955080, Email ganwenjuan@suda.edu.cnAbstract: The Wnt/β-catenin signaling pathway is a growth control pathway involved in various biological processes as well as the development and progression of cancer. Colorectal cancer (CRC) is one of the most common malignancies in the world. The hyperactivation of Wnt signaling is observed in almost all CRC and plays a crucial role in cancer-related processes such as cancer stem cell (CSC) propagation, angiogenesis, epithelial-mesenchymal transition (EMT), chemoresistance, and metastasis. This review will discuss how the Wnt/β-catenin signaling pathway is involved in the carcinogenesis and progression of CRC and related therapeutic approaches.Keywords: Wnt pathway, colorectal carcinogenesis, APC, CRC therapy